Visual Design of Riau Malay Songket Weaving Motif Application (Case Study of Riau Malay Siak Songket Fabric Motif) - Randa, R A; Maulina, R (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This scientific work aims to compile a visual application of information about the Riau Malay Songket Weaving Motif, especially in the Siak area. By using the Visual Communication design method with visual application design on the device with the source of library materials, interviews, and questionnaires conducted on the community in the city of Pekanbaru, men and women aged 20-25 years. The result of the research is a visual design of the Riau Malay Songket Weaving Motif application on the Siak Malay Motif as a case study because there are so many types. Songket Siak fabrics have various motifs, colors, and meanings. The general public prefers the Malay Siak songket cloth from its beauty alone, the philosophical content that is very valuable on the Songket cloth is not much seen. Existing media information also discusses more in terms of the beauty of motifs and colors, less media contains information about the meaning of the Riau Malay Songket cloth, especially Songket Siak. The meaning of the Siak Malay Songket cloth as part of the identity of the Riau Malay community does not need to be known. By looking at the philosophical meaning of the Siak Malay songket motif, it can add to the love of Riau Malay culture and increase the pride of being a Riau Malay community, especially for the younger generation. It is hoped that the availability of this application can add information about the Riau Malay songket weaving motif, especially the Siak Malay Songket Motif for the younger generation.